2020
DOI: 10.1002/cdq.12219
|View full text |Cite
|
Sign up to set email alerts
|

Career Adaptability and Turnover Intention: A Dual‐Mediation Model

Abstract: Career adaptability denotes psychosocial resources that help employees self-manage career change through both adapting themselves to the environment and adapting the environment to themselves. Previous studies have probed the former strategy and proposed a negative relationship between career adaptability and turnover intention. However, the presence of the latter strategy suggests a more complex relationship than previously thought. From a person-job fit perspective, the authors used structural equation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The current study found that self-efficacy had a mediating effect on the relationship between perceived overqualification and turnover intention, opening up understandings around the effect of the perceived over-qualification cognitive path (the "black box") on turnover intention and testing the transmission mechanism of self-efficacy between perceived overqualification and turnover intention. Responding to the research suggestions of Hu et al (2015) and Dong et al (2020), these findings broaden our understandings of another mediation path concerning perceived over-qualification and its outcome variables. Perceived over-qualification was found to significantly positively affect self-efficacy.…”
Section: (P < 001) Yesmentioning
confidence: 60%
See 1 more Smart Citation
“…The current study found that self-efficacy had a mediating effect on the relationship between perceived overqualification and turnover intention, opening up understandings around the effect of the perceived over-qualification cognitive path (the "black box") on turnover intention and testing the transmission mechanism of self-efficacy between perceived overqualification and turnover intention. Responding to the research suggestions of Hu et al (2015) and Dong et al (2020), these findings broaden our understandings of another mediation path concerning perceived over-qualification and its outcome variables. Perceived over-qualification was found to significantly positively affect self-efficacy.…”
Section: (P < 001) Yesmentioning
confidence: 60%
“…Accordingly, the current study identified several shortcomings in the literature review conducted. First, the existing research pays greater attention to the positive impact of perceived over-qualification on individuals, such as organizational citizenship behavior (Chen and Kao, 2011;Elamin and Tlaiss, 2015;Luksyte and Spitzmueller, 2016) and job satisfaction (Lee et al, 2013;Yang et al, 2015;Dong et al, 2020;García-Mainar and Montuenga-Gómez, 2020). Additionally, a few studies have explored the negative impact of perceived over-qualification on individuals, such as antiproductive behavior (Bolino and Feldman, 2000;Zhang et al, 2016;Schreurs et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we collected objective data of employment status from the target company as the indicator of turnover behavior. Previous studies examined turnover intention rather than actual turnover (Chan et al, 2016; Chan & Mai, 2015; Dong et al, 2020; Guan et al, 2015; Ito & Brotheridge, 2005; Zhu et al, 2019), with the assumption that leaving intention serves equally well as both a proxy for and a predictor of employees' actual turnover behavior. However, turnover intention and actual turnover are two distinct concepts, so the intention–behavior relation has varied widely across studies (Cohen et al, 2016; Vandenberg & Nelson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Another implication is that the current research contributed a new possibility regarding the effect of CA on turnover, namely, that CA enables employees to develop their careers by casting their sights outside their current organizations, leading to subjective evaluations of deprivation and actual turnover behavior. In fact, a large body of existing research only supports a one‐sided view of the relationship while paying little attention to the effects of CA outside the current organization (to the best of our knowledge, for CA‐external employability; see Spurk et al, 2016; for CA‐perceived over‐qualification, see Dong et al, 2020). Hence, our study pictured a comprehensive model to broaden the focus to a wider career ecosystem through both internal‐orientated and external‐orientated mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies of CA and work transitions to date (all crosssectional, survey based) have only focused on organizational turnover intention and for Chinese workers only (e.g., Haibo et al, 2017). In contrast with greater ability to change (see Savickas & Porfeli, 2012), all studies found negative associations between CA and organizational turnover intention, mostly explained via job satisfaction (Dong et al, 2020;Johnston, 2018).…”
mentioning
confidence: 99%